Potensi Bunga Telang dan Daun Stevia Sebagai Bahan Teh Herbal Dengan Variasi Suhu dan Lama Pengeringan - Titik Suryani; Nevia Gina Pradita (Universitas Sebelas Maret, 2025)
Herbal tea is a beverage product made from plant leaf beneficial for health and refreshing drink. One of the innovative ingredients of herbal tea is butterfly pea flowers and stevia leaf. Butterfly pea flowers (Clitoria ternatea L) contain flavonoids, anthocyanins, glycosides, and kaempferol glycosides as antioxidant compounds that prevent free radicals. The addition of stevia leaf (Stevia rebaudiana) as a natural sweetener, low calories and as a substitute of sugar. The aim of this research was to determine the antioxidant activity and organoleptic quality of herbal tea combination between butterfly pea flowers and stevia leaf on variations of temperature and drying duration. This research method was experimental with a Completely Randomized Design (CRD), two treatment factors. The first factor was variation of drying temperature (T) at 55˚C and 60˚C and the second factor was variation of drying duration (L) 70 minutes, 90 minutes and 120 minutes. The results showed that the highest antioxidant activity of herbal tea combination between butterfly pea flowers and stevia leaf in the T2L1 treatment (temperature 60˚C and drying duration 70 minutes) was 88.811%. The best organoleptic quality of herbal tea in the T2L1 treatment was purple ,ordinary aroma,not bitter taste and sweet, liked.